A Method of Facilitating Mobility in Children Undergoing Halo Skeletal Traction. Issue 3 (July 2018) - Mullan, Betsy; Turner-Bare, Karen R.; Pedicone, Dave; Shannon, Christina; Kane, Meghan; Hancock, Sarah; Rahman, Tariq; Ditro, Colleen; Mackenzie, William; Gabos, Peter; Shah, Suken A.
Abstract : The earliest documented use of skeletal traction devices was detailed by Hippocrates. From the Middle Ages through to the evolution of modern medicine, patients undergoing skeletal traction were confined to bed. Early to mid-1900s studies document the use of a halo to apply skeletal traction to manage spinal deformities. Adapted wheelchairs for halo traction were developed in the mid-1900s. Our halo traction program team modified wheelchairs and walkers to provide out-of-bed mobility. Optimization of patient independence during mobility in halo traction and the staff's ability to manage increasing amounts of halo traction weight were considered during program development.